The Measurement and Trend of Inequality: Comment - Danziger, Sheldon; Haveman, Robert; Smolensky, Eugene (American Economic Review, 2016)
In the September 1975 issue of this Review, Morton Paglin posits a new summary statistic, the Paglin-Gini, which he uses to measure and analyze the level and trend of income inequality in the United States. This measure intends to recognize only income differences among families unrelated to the observed age-income profile as contributing to meaningful income inequality. This is to be contrasted with the standard Lorenz-Gini, in which all differences in income among living units contribute to inequality. Paglin's measure indicates substantially less inequality in the United States than is indicated by the Lorenz-Gini. Moreover, Paglin-inequality falls considerably in the post-World War II period while other measures indicate very little change in inequality over this period. Paglin is addressing an important problem. For the postwar period when the age distribution, the length of time spent in school, and the propensity of the young and the old to form their own households have all changed rapidly, the trend in the conventional Gini coefficient has no obvious normative interpretation. However, it is often given one. Unfortunately, Paglin's proposed index of inequality does not meet its objective and, even if it did, its normative content would be no clearer than that of the standard measure. Indeed, no single indicator is sufficient to capture trends in normatively relevant inequality without further analysis. Like any other time-series, a time-series of inequality must be approached with a well-specified, multivariate model. After describing Paglin's procedure in the next section, we challenge his measure in Section II. In Section III, Paglin's interpretation of policy-relevant inequality is questioned, and in Section IV the implications of the Paglin-Gini for the equity of the transfer system are analyzed. Section V is a summary of our critique.